1978
DOI: 10.1017/s0003356100040848
|View full text |Cite
|
Sign up to set email alerts
|

Growth of bovine tissues 1. Genetic influences on growth patterns of muscle, fat and bone in young bulls

Abstract: Carcass composition and growth patterns for muscle, fat and bone were compared among 277 young male progeny of eight sire breeds, serially slaughtered at 300 kg live weight, 12 months and 15 months of age. The sire breeds were Simmental (SIM), Charolais (CHA), Danish Red and White (DRK), Romagnola (ROM), Chianina (CHI), Hereford (HER), Blonde d'Aquitaine (BDA) and Limousin (LIM). Tissue growth patterns among breeds were examined by regression estimates from the allometric growth equation (Y = ax h ) and compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
3
5

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 13 publications
6
48
3
5
Order By: Relevance
“…Os animais foram separados aleatoriamente em cinco grupos, compostos por cinco animais de cada grupo gené-tico. Um dos grupos foi abatido no início do experimento e os demais permaneceram em sistema de criação em pasto, com suplementação nutricional, sendo abatidos de forma seriada ao longo de 204 dias, possibilitando a obtenção de animais em faixas crescentes de peso (Berg et al, 1978).…”
Section: Methodsunclassified
“…Os animais foram separados aleatoriamente em cinco grupos, compostos por cinco animais de cada grupo gené-tico. Um dos grupos foi abatido no início do experimento e os demais permaneceram em sistema de criação em pasto, com suplementação nutricional, sendo abatidos de forma seriada ao longo de 204 dias, possibilitando a obtenção de animais em faixas crescentes de peso (Berg et al, 1978).…”
Section: Methodsunclassified
“…In this regard, Mukhoty and Berg (1971) and Charles and Johnson (1976) reported breed differences in the rate of fat deposition, but Berg et al (1978a), working with breeds classified as late fattening, reported homogeneous allometric regression coefficients for fat deposition among sire breed groups.…”
Section: Resultsmentioning
confidence: 96%
“…Kempster et al (1976a), working with differ ent breeds, and Berg et al (1978a), using cattle of the three sexes, reported an increase in the ratio of subcutaneous: intermuscular fat with fattening. The discrepancies may be explained by differences in the cattle used and by the inclu sion of omental and mesenteric fat depots in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O tecido ósseo apresenta maior impulso de crescimento em menor idade, enquanto o tecido adiposo tem crescimento em idade mais avançada e o tecido muscular, em idade intermediária (Berg et al, 1978;Müller e Primo, 1986 (2012) com codornas de corte machos e fêmeas abatidas em diferentes idades, houve efeito no desenvolvimento alométrico para o desenvolvimento do osso do peito e da asa para os machos na idade de 35 dias, os quais apresentaram desenvolvimentos precoces (b<1) dado semelhante ao encontrado no presente estudo.…”
Section: Resultsunclassified